2006
DOI: 10.1300/j457v02n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Conversations at the End of Life

Abstract: Oregon's Death with Dignity Act (ODWDA) has been in effect for eight years. The United States Supreme Court recently decided that Oregon's law did not violate the Controlled Substances Act. Other states may consider a law similar to Oregon's through legislative process or ballot measures. Although social work is not mentioned in the law, our profession interfaces with the terminally ill, particularly in hospice. Eighty-seven percent of those who have used the law were enrolled in a hospice program. As a pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Titles and abstracts were reviewed against these criteria by S. M. G. and G. K., who then reviewed 105 full-text articles and in collaboration with all team members, agreed on the final 16 articles for inclusion. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 To present the data, a spreadsheet was created with column headings denoting study design, date and location of data collection, population and setting studied, key findings, and explicit or implied relationship of assisted dying to palliative care. Findings from the studies were then extracted from the results, discussions, and conclusions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Titles and abstracts were reviewed against these criteria by S. M. G. and G. K., who then reviewed 105 full-text articles and in collaboration with all team members, agreed on the final 16 articles for inclusion. 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 To present the data, a spreadsheet was created with column headings denoting study design, date and location of data collection, population and setting studied, key findings, and explicit or implied relationship of assisted dying to palliative care. Findings from the studies were then extracted from the results, discussions, and conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…About 95% of all surveyed report that hospices should be either supportive or remain neutral Explicit and implied: supportive, neutral, not mutually exclusive Most hospice professionals in Oregon do not believe that assisted suicide and hospice enrolment are mutually exclusive alternatives Miller et al. 43 Qualitative pilot project—exploring experiences of the three authors who are social workers After implementation of law. Year unspecified Oregon, U.S. Social workers in health systems, outpatient, and acute care settings Some concerns identified that the Death with Dignity Act is at odds with hospice philosophy, especially in religious institutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation